The Design a System of Retention and Control on Broiler Farms Based on the Flow of Data - Ahmad Sanmorino; Isabella Isabella (IAES Indonesia Section, 2017)
In this study, we tried to design a system of retention and control on broiler farms in Prabumulih based on the data flow between processes, external entity and data storage. The purpose of this study was to find the best design that can be immediately implemented in the form of information systems. The design submitted is expected to accelerate the process that occurs between entities connected. Minimizing the possibility of error, which in turn can increase the production of broiler when the harvest is done.